Taking the ‘human’ out of humanitarian? States’ positions on Lethal Autonomous Weapons Systems from an International Humanitarian Law perspective - Neth, Henrik (Riga Graduate School of Law, 2019)
The debate about the legality of Lethal autonomous weapons systems (LAWS) under humanitarian law is still ongoing. This is also due to the developing of autonomous weapon systems which might reach new milestones in autonomous technology. Thus, new legal reviews would be required. The research question of this thesis asks: In how far are lethal autonomous weapons systems in compliance with international humanitarian law and how strict is it interpreted by individual states? At first, this research examines and conceptualizes the characteristics of autonomous weapons and conducts a legal analysis on humanitarian law. LAWS are characterized by their amount of human control, the sophistication of autonomy, and functions they have.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; International humanitarian law